Effects of heavy alkali elements in Cu(In, Ga)Se2 solar cells with efficiencies up to 22.6%. Issue 8 (12th July 2016) - Jackson, Philip; Wuerz, Roland; Hariskos, Dimitrios; Lotter, Erwin; Witte, Wolfram; Powalla, Michael
Abstract : We report on the use and effect of the alkali elements rubidium and caesium in the place of sodium and potassium in the alkali post deposition treatment (PDT) as applied to Cu(In, Ga)Se2 (CIGS) solar cell absorbers. In order to study the effects of the different alkali elements, we have produced a large number of CIGS solar cells with high efficiencies resulting in a good experimental resolution to detect even small differences in performance. We examine the electrical device parameters of these fully functional devices and observe a positive trend in the I – V parameters when moving from devices without PDT to KF‐, RbF‐, and eventually to CsF‐PDT. A diode analysis reveals an improved diode quality for cells treat‐ed with heavier alkalis. Furthermore, secondary ion mass spectrometry (SIMS) measurements reveal a competitive mechanism induced within the class of alkali elements in the CIGS absorber induced by the alkali post deposition treatment. (© 2016 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : A new world record efficiency for thin film solar cells of 22.6% has been achieved with a rubidium fluoride post‐deposition treatment. The authors compare treatments using lighter and heavier alkali elements as applied to the Cu(In, Ga)Se2 absorber. An interesting competitive behaviour of the various alkali elements in this functional layer of the solar cell is described.